1998
DOI: 10.1172/jci1581
|View full text |Cite
|
Sign up to set email alerts
|

Retinoids increase human apo C-III expression at the transcriptional level via the retinoid X receptor. Contribution to the hypertriglyceridemic action of retinoids.

Abstract: Hypertriglyceridemia is a metabolic complication of retinoid therapy. In this study, we analyzed whether retinoids increase the expression of apo C-III, an antagonist of plasma triglyceride catabolism. In men, isotretinoin treatment (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(92 citation statements)
references
References 55 publications
9
81
0
2
Order By: Relevance
“…19 In support of this claim, we observed that the RXR agonist LG100268, but not the antagonist LG100754, stimulated TG synthesis in HepG2 cells. One proposal suggests that PIs alter RXR signaling by inhibiting the synthesis of 9-cis-retinoic acid.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…19 In support of this claim, we observed that the RXR agonist LG100268, but not the antagonist LG100754, stimulated TG synthesis in HepG2 cells. One proposal suggests that PIs alter RXR signaling by inhibiting the synthesis of 9-cis-retinoic acid.…”
Section: Discussionsupporting
confidence: 51%
“…19 To investigate whether retinoids and PIs interact to increase hepatic lipid synthesis, HepG2 cells were treated with NFV in the absence or presence of the RXR agonist LG100268 or the RXR homodimer antagonist LG100754. As shown in Figure 2A, 100 nmol/L LG100754 did not significantly affect TG synthesis.…”
Section: Nfv and Lg100268 Stimulate Lipid Synthesis And Gene Expressimentioning
confidence: 99%
“…RBP4 is a transporter protein for retinol that serves as a precursor for the synthesis of ligands of the retinoid X receptor and retinoic acid receptor nuclear hormone receptors [19]. In previous studies, retinoids increased the hepatic production of VLDL [20] and elevated the levels of apolipoprotein (apo) C-III [21], a hepatic protein that delays (1) the catabolism of VLDL particles by inhibiting their binding to the endothelial surface and (2) lipolysis by lipoprotein lipase [22]. This may explain the lack of an association between RBP4 and lipoprotein lipase in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Both fibratesFagonists of peroxisome proliferator-activated receptor alpha (PPARa)Fand retinoidsFpanagonists of the retinoic acid receptors RAR and RXRFwere commonly shown to influence triglyceridemia through changing the expression of apolipoprotein C-III (ApoC-III) gene. 6,7 This gene alone as well as the whole ApoA-I/C-III/A-IV cluster (and most recently its new member, ApoA-V) were associated with dyslipidemia in human populations and animal models 3,8 and were also suggested as putative candidates for hypertriglyceridemia in a genetic model of insulin resistance syndrome, polydactylous (PD/Cub) rat strain [9][10][11][12][13][14] (http:// www.img.cas.cz/fb/, Table 1). Therefore, we examined the effect of fenofibrate and isotretinoin administration on metabolic profile, insulin sensitivity and lipolysis in tissues and the expression of ApoC-III and one of its proposed upstream regulatory genes, hepatocyte nuclear factor-4 (Hnf-4), in the PD/Cub rat strain.…”
Section: Introductionmentioning
confidence: 99%